Medetomidine may cause heart murmur in Cougars and Jaguars: case report - Luczinski, Thiago Cavalheri; de Araújo, Gediendson Ribeiro; Silveira, Matheus Folgearini; Kirnew, Murillo Dapare [UNESP]; Navarrete, Roberto Andres [UNESP]; Salomão-Jr, Jorge Aparecido; Requena, Leticia Alecho; Melo dos Santos, Jairo Antonio; Koshiyama, Marcell Hideki; Pizzutto, Cristiane Schilbach; Jorge-Neto, Pedro Nacib (Wildlife Information Liaison Development Society, 2020)
We report heart murmur in Jaguars and Cougars found during reproductive procedures for semen and oocyte collection. Two male Cougars (n=2) and three female Jaguars (n=3) were examined. Anesthesia was performed with ketamine and medetomidine in males. Females also received propofol and were maintained with isoflurane. The animals were evaluated during anesthetic monitoring with multiparameter monitor alongside clinical examination, ambulatory electrocardiogram and echocardiogram. All animals presented mitral valve regurgitation under anesthesia, but without morphological changes in the cardiac structure or hemodynamic changes. Medetomidine may cause transitory heart murmur in healthy Jaguars and Cougars.
Keywords: a-2 adrenoceptor agonist; mitral valve regurgitation; trivial tricuspid valve regurgitation